Classifying motor coordination impairment in Para swimmers with brain injury. Issue 5 (May 2019) - Hogarth, Luke; Payton, Carl; Nicholson, Vaughan; Spathis, Jemima; Tweedy, Sean; Connick, Mark; Beckman, Emma; Van de Vliet, Peter; Burkett, Brendan
Abstract: Objectives: The International Paralympic Committee has mandated that International Sport Federations develop sport-specific classification systems that are evidence-based. This study examined the predictive and convergent validity of instrumented tapping tasks to classify motor coordination impairments in Para swimming. Design: Cross-sectional. Methods: Thirty non-disabled participants and twenty-one Para swimmers with brain injury completed several instrumented tapping tasks as an assessment of upper and lower limb motor coordination. Para swimmers also completed a maximal freestyle swim to obtain a performance measure. The predictive and convergent validity of instrumented tapping tasks was examined by establishing differences in test measures between participants with and without brain injury and defining the strength of association between test measures and maximal freestyle swim speed in Para swimmers, respectively. Results: Random forest successfully classified 96% of participants with and without brain injury using test measures derived from instrumented tapping tasks. Most test measures had moderate to high correlations (r = 0.54 to 0.72; p < 0.01) with maximal freestyle swim speed and collectively explained up to 72% of the variance in maximal freestyle swim performance in Para swimmers with brain injury. Conclusions: The results of this study evidence the predictive and convergent validity of instrumented tapping tasks to classify motor coordination impairments in Para swimmers with brain injury. These tests can be included in revised Para swimming classification to improve the objectivity and transparency in determining athlete eligibility and sport class for these Para athletes.